On the causes of the distress at Skull and Skibbereen, during the famine in Ireland - Hancock, W. Neilson (Statistical and Social Inquiry Society of Ireland, 1851)
In this paper I propose to direct your attention to some statistical information which throws considerable light on the real causes of distress in Ireland. The information relates to a tract of land situate in the southwest of Cork, and lying between the village of Skull and the town of Skibbereen. There is scarcely any part of Ireland which suffered so much during the famine of 1846 and 1847 as the district around Skibbereen. Indeed, the name of that town has become in Ireland almost synonymous with distress. I shall then proceed to investigate the causes to which this extreme distress may be ascribed. In proceeding with this investigation, the first consideration which naturally presents itself is, Was this distress entirely caused by the potato failure? To answer this question, it will be necessary to inquire what was the state of the Skibbereen district before 1846.
A paper read before the statistical section of the British association, at Edinburgh, August 2nd, 1850.
Keywords: South west Cork; Famine; 314.15